Isolation and Nitrogen Removal Efficiency of the Heterotrophic Nitrifying-Aerobic Denitrifying Strain K17 From a Rare Earth Element Leaching Site - Hu, Jingang; Yang, Xinyu; Deng, Xiangyi; Liu, Xuemei; Yu, Junxia; Chi, Ruan; Xiao, Chunqiao (Frontiers in Microbiology, 2022)
K17, an indigenous and heterotrophic nitrifying-aerobic denitrifying bacterium was isolated from the soil of a weathered crust elution-deposited rare earth ore leaching site in Longnan County, China. Strain K17 was identified as Pseudomonas mosselii. In this study, the morphological characteristics of strain K17 were observed and the optimal ammonia nitrogen removal conditions for the strain were studied using a single-factor experiment. Key enzyme activities were determined, and we also explored the ammonia nitrogen removal process of strain K17 on simulated leaching liquor of the rare earth element leaching site. Based on the determination of ammonia nitrogen removal and enzyme activity, it was found that strain K17 has both heterotrophic nitrifying and aerobic denitrifying activities. In addition, single-factor experiments revealed that the most appropriate carbon source for strain K17 was sodium citrate with a C/N ratio of 10 and an initial NH4+-N concentration of 100 mg/L. Furthermore, the optimal initial pH and rotation speed were 7 and 165 r/min, respectively. Under optimal conditions, the ammonia nitrogen removal efficiency of strain K17 was greater than 95%. As an indigenous bacterium, strain K17 has great potential for treating residual ammonium leaching solutions from rare earth element leaching sites.